2023
DOI: 10.1186/s12985-023-01971-x
|View full text |Cite
|
Sign up to set email alerts
|

Bafilomycin A1 inhibits SARS-CoV-2 infection in a human lung xenograft mouse model

Abstract: Coronavirus disease 2019 is a global pandemic caused by SARS-CoV-2. The emergence of its variant strains has posed a considerable challenge to clinical treatment. Therefore, drugs capable of inhibiting SARS-CoV-2 infection, regardless of virus variations, are in urgently need. Our results showed that the endosomal acidification inhibitor, Bafilomycin A1 (Baf-A1), had an inhibitory effect on the viral RNA synthesis of SARS-CoV-2, and its Beta and Delta variants at the concentration of 500 nM. Moreover, the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We, therefore, infected TMPRSS2-expressing Vero-E6 cells treated with the DPUDs with SARS-CoV-2 (D614G) in presence/absence of camostat. We also included BafA1 and niclosamide as they have been reported to attenuate SARS-CoV-2 infection [ 19 , 69 , 71 , 72 ]. BafA1 is a vATPase inhibitor and niclosamide is a protonophore that disrupts proton gradient, and both the drugs potently inhibit endosomal acidification.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, infected TMPRSS2-expressing Vero-E6 cells treated with the DPUDs with SARS-CoV-2 (D614G) in presence/absence of camostat. We also included BafA1 and niclosamide as they have been reported to attenuate SARS-CoV-2 infection [ 19 , 69 , 71 , 72 ]. BafA1 is a vATPase inhibitor and niclosamide is a protonophore that disrupts proton gradient, and both the drugs potently inhibit endosomal acidification.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that MHV infection induces ER-derived double-membrane vesicles (DMVs) independent of the autophagic pathway through the hijacking of the host cell ERassociated degradation (ERAD) machinery [46]. Recently, reports showed that applying the inhibitors that block the fusion between autophagosomes and lysosomes to coronaviruses' infected cells can potentially decrease the viral infection [47][48][49]. We, therefore, assessed whether G42 inhibits infection of MHV in its host cells.…”
Section: G42 Inhibits Zikv and Mhv Infections Of Host Cellsmentioning
confidence: 99%